The Relationship Between Apolipoprotein ε4 Carrier Status and Sleep Characteristics in Cognitively Normal Older Adults. (September 2017) - Kahya, Melike; Vidoni, Eric; Burns, Jeffrey M.; Thompson, Ashley N.; Meyer, Kayla; Siengsukon, Catherine F.
The apolipoprotein (APOE) ε4 allele, a well-described genetic risk factor for late-onset Alzheimer disease (AD), is associated with sleep disturbances even in cognitively normal older adults, although it is not clear whether this association is independent of sleep apnea. We sought to extend previous studies by examining whether cognitively normal older adults without self-reported sleep apnea who carry the APOE ε4 allele have altered sleep characteristics compared to noncarriers. Data from N = 36 (APOE ε4 carriers [n = 9], noncarriers [n = 27]) cognitively normal older adults (Clinical Dementia Rating [CDR] scale = 0) without self-reported sleep apnea were used for these analyses. Participants wore an actigraph for 7 days to determine sleep characteristics. The Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS) were used to assess sleep quality and daytime sleepiness, respectively. The APOE ε4 carriers had a higher number of awakenings compared to the noncarriers ( P = .02). There was no significant difference in the PSQI global score and the ESS; however, the PSQI subcomponent of daily disturbances was significantly higher in APOE ε4 carriers ( P = .03), indicating increased daytime dysfunction is related to disrupted sleep. This study provides evidence that individuals who are cognitively normal and genetically at risk of AD may have disrupted sleep. These findings are consistent with prior studies and suggest that sleep disruption may be present in the presymptomatic stages of AD.